Sexually dimorphic leanness and hypermobility in p16 Ink4a /CDKN2A-deficient mice coincides with phenotypic changes in the cerebellum - Kwang H. Kim (Nature Portfolio, 2019)
Abstract p16 Ink4a /CDKN2A is a tumor suppressor that critically regulates the cell cycle. Indeed, p16 Ink4a deficiency promotes tumor formation in various tissues. We now report that p16 Ink4a deficiency in female mice, but not male mice, induces leanness especially in old age, as indicated by lower body weight and smaller white adipose tissue, although other major organs are unaffected. Unexpectedly, the integrity, number, and sizes of adipocytes in white adipose tissue were unaffected, as was macrophage infiltration. Hence, hypermobility appeared to be accountable for the phenotype, since food consumption was not altered. Histological analysis of the cerebellum and deep cerebellar nuclei, a vital sensorimotor control center, revealed increased proliferation of neuronal cells and improved cerebellum integrity. Expression of estrogen receptor β (ERβ) and PCNA also increased in deep cerebellar nuclei, implying crosstalk between p16 Ink4a and ERβ. Furthermore, p16 Ink4a deficiency expands LC3B+ cells and GFAP+ astrocytes in response to estrogen. Collectively, the data suggest that loss of p16 INK4a induces sexually dimorphic leanness in female mice, which appears to be due to protection against cerebellar senescence by promoting neuronal proliferation and homeostasis via ERβ.